2015
DOI: 10.1007/978-3-319-16862-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conducting Polymers

Abstract: A conjugated polymer in neutral state is semiconductive. It becomes conductive after it is doped by oxidation or reduction. The optical properties of neutral conjugated polymers are predominantly determined by the electron transition from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO), whereas the optical properties of conducting polymers are related to new energy levels, polaron and bipolaron levels, which are generated during oxidation or reduction. The appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 108 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Band theory is based on Hückel’s molecular orbital theory (HMO) and was used at the end of the 1970s by Brédas to understand the CP properties known until then. , It has been continuously invoked to explain several CP properties. , Theoretical calculations suggest three absorption bands for the polaron and two for the bipolaron states, , and they have been experimentally observed in numerous CP absorption spectra (Figure ). …”
Section: Interrelationship Between Electrochemistry and Conducting Po...mentioning
confidence: 56%
See 1 more Smart Citation
“…Band theory is based on Hückel’s molecular orbital theory (HMO) and was used at the end of the 1970s by Brédas to understand the CP properties known until then. , It has been continuously invoked to explain several CP properties. , Theoretical calculations suggest three absorption bands for the polaron and two for the bipolaron states, , and they have been experimentally observed in numerous CP absorption spectra (Figure ). …”
Section: Interrelationship Between Electrochemistry and Conducting Po...mentioning
confidence: 56%
“…Many of the interesting properties of CPs like optical response, ionic and electronic conductivity, surface tension, volume change, and tunable band-gaps , are direct consequences of the solid state redox reactions known as polymer charging/discharging (see section , Figure ), and have been exploited for technological applications (Table ). These properties can be controlled with the doping level of the material, and new possibilities for a wide range of industrial applications , are being developed.…”
Section: Interrelationship Between Electrochemistry and Conducting Po...mentioning
confidence: 99%
“…The chemistry, structure, and electronic transport properties have been reviewed in detail in some recent publications by Xia et al [63], Kayser and Lipomi [64], and very recently by Gueye et al [65] and by Huseynova et al [66].…”
Section: Conductive Polymers Pedot:pssmentioning
confidence: 99%
“…One of the main drawbacks of PEDOT:PSS is associated with its relatively low inherent conductivity, which is usually below 1 S/cm. To improve conductivity, several methods, such as the addition of high-boiling-point polar organic solvents, ionic liquids, or surfactants; post-treatment with organic solvents, polar solvent vapor, salts, zwitterions, or acids; and combinations of these, have been explored, resulting in an increase in conductivity by two or three orders of magnitude [15][16][17][18][19][20]. Recently reported results demonstrated that it is possible to enhance the conductivity of PEDOT:PSS films to more than 4000 S/cm [21], which is comparable to that of indium tin oxide (ITO) and allows the PEDOT:PSS films to be used as transparent electrodes of touchscreens and solar cells.…”
Section: Introductionmentioning
confidence: 99%